2017
DOI: 10.1097/aln.0000000000001660
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review and Meta-analysis Examining the Impact of Incident Postoperative Delirium on Mortality

Abstract: Background Delirium is an acute and reversible geriatric syndrome that represents a decompensation of cerebral function. Delirium is associated with adverse postoperative outcomes, but controversy exists regarding whether delirium is an independent predictor of mortality. Thus, we assessed the association between incident postoperative delirium and mortality in adult noncardiac surgery patients. Methods A systematic search wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
64
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 93 publications
(69 citation statements)
references
References 62 publications
4
64
1
Order By: Relevance
“…26 As opposed to a longer length of stay observed in other studies, we achieved an earlier discharge, possibly accounting for the high percentage of HF dementia patients coming from nursing homes. 5 According to the current literature and the positive outcomes of our study, involving geriatricians in the implementation of specific strategies for the prevention of delirium in HF patients might reduce adverse outcomes associated with delirium. 27 However, and in line with our results, a recent metaanalysis showed that delirium was not significantly associated with mortality.…”
Section: Variablementioning
confidence: 77%
See 2 more Smart Citations
“…26 As opposed to a longer length of stay observed in other studies, we achieved an earlier discharge, possibly accounting for the high percentage of HF dementia patients coming from nursing homes. 5 According to the current literature and the positive outcomes of our study, involving geriatricians in the implementation of specific strategies for the prevention of delirium in HF patients might reduce adverse outcomes associated with delirium. 27 However, and in line with our results, a recent metaanalysis showed that delirium was not significantly associated with mortality.…”
Section: Variablementioning
confidence: 77%
“…5 The ability to carry out the ADL was classified according to the usual cut-off points of the BI. Patients' walking ability was classified by the Red Cross Physical Scale 16 into able to walk independently (0-2), able to walk with the assistance of other persons 3,4 and unable to walk.…”
Section: Variables and Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…30 The strengths of this study include its prospective perioperative design, statistical methods chosen, and rigorous delirium assessments including outcomes based on severity and incidence of delirium. Furthermore, a recent systematic review questioned the strength of the association between postoperative delirium and mortality; hence, a priori we hypothesized that NSQIP-SC would perform better than NSQIP-D for predicting postoperative delirium severity and incidence.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, an individual with fewer predisposing risk factors will require a large stimulus to precipitate delirium. 30 As delirium is a cognitive disorder, we further hypothesized that cognitive data (that are not included in the NSQIP calculation) could enhance the prediction of the surgical risk scores. The online surgical risk calculator built and copyrighted by the American College of Surgeons, National Surgical Quality Improvement Program (ACS NSQIP), may be ideal for delirium severity prediction as it includes several predisposing risk factors and the estimated magnitude of the precipitating event, the surgery.…”
mentioning
confidence: 99%